2019
DOI: 10.1002/ecy.2790
|View full text |Cite
|
Sign up to set email alerts
|

Good neighbors aplenty: fungal endophytes rarely exhibit competitive exclusion patterns across a span of woody habitats

Abstract: Environmental forces and biotic interactions, both positive and negative, structure ecological communities, but their relative roles remain obscure despite strong theory. For instance, ecologically similar species, based on the principle of limiting similarity, are expected to be most competitive and show negative interactions. Specious communities that assemble along broad environmental gradients afford the most power to test theory, but the communities often are difficult to quantify. Microbes, specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 90 publications
1
33
0
Order By: Relevance
“…Ascomycete insect pathogens are closely related to plant pathogens and endophytes [ 42 ]. The DNA barcoding analysis of wood endophytes revealed that CEP was not applicable to these fungi since diverse fungal taxa were co-present in wood samples [ 43 ]. Instead, the model of competition–colonization tradeoffs has been suggested to mediate the competition and coexistence of the fungal mycorrhiza or pathogens since the diverse species of these fungi could either occupy different root tips [ 13 , 44 , 45 ] or infect different parts of individual plants [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ascomycete insect pathogens are closely related to plant pathogens and endophytes [ 42 ]. The DNA barcoding analysis of wood endophytes revealed that CEP was not applicable to these fungi since diverse fungal taxa were co-present in wood samples [ 43 ]. Instead, the model of competition–colonization tradeoffs has been suggested to mediate the competition and coexistence of the fungal mycorrhiza or pathogens since the diverse species of these fungi could either occupy different root tips [ 13 , 44 , 45 ] or infect different parts of individual plants [ 34 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, microbes are the key decay agents but their decay abilities are shaped by environmental conditions and biotic interactions. To date, we have had a poor understanding of what regulates wood‐decay community structure and function through time (Lee et al ., 2019). This study shows that environmental factors that predict decay rates (Zanne et al ., 2015) have the same rank importance in structuring deadwood microbial communities in a temperate deciduous oak‐hickory forest.…”
Section: Discussionmentioning
confidence: 99%
“…While generally considered to be “just” saprotrophs, some studies also report Mollisia as endophytes of leaves and twigs in diverse host plants ( Sieber, 1989 , Barklund and Kowalski, 1996 , Shamoun and Sieber, 2000 , Kowalski and Andruch, 2012 , Anderson Stewart et al. 2019 , Lee et al. 2019 ).…”
Section: Introductionmentioning
confidence: 99%